Perancangan UI/UX Aplikasi Feedback Pengunjung Kambang Iwak Menggunakan Metode Design Thinking - Dharmananda Dharmananda; Vionetha Lavega; Vivian Vivian; Agnes Monica; Ahmad Farisi (Universitas Multi Data Palembang, 2026)
This study aims to design the UI/UX of a visitor feedback application for Taman Kambang Iwak Palembang as a solution to the absence of an official medium for conveying visitor aspirations, suggestions, and complaints. The scope of the study focuses on the design of the user interface and user experience of a mobile application that is oriented toward user needs. The method employed is Design Thinking, which consists of the empathize, define, ideate, prototype, and test stages. The results of the study include a prototype of a visitor feedback application that provides features such as cleanliness reporting, damaged facility reporting, satisfaction surveys, and general feedback with a simple user flow. Usability testing was conducted using the System Usability Scale (SUS) with 12 respondents and yielded an average score of 73.75, which falls into the Good and Acceptable categories. These findings indicate that the proposed UI/UX design has a good level of usability and is well accepted by users. Therefore, the application has the potential to assist management in systematically collecting visitor feedback and supporting improvements in the management quality of Taman Kambang Iwak Palembang.